963 PRELIMINARY OBSERVANIONAL STUDY ON CARDIAC REMODELING IN PATIENTS UNDERGOING EDGE-TO-EDGE TRANS-CATHETER MITRAL VALVE REPAIR WITH MITRA CLIP DEVICE. (15th December 2022) - Coppi, Francesca; Manenti, Antonio; Mattioli, Anna Vittoria; Sgura, Fabio; Passiatore, Matteo; Coppi, Giovanni; Boriani, Giuseppe
Abstract: Preliminary Observational Study on Cardiac Remodeling in Patients Undergoing Edge-to-Edge Trans-catheter Mitral Valve Repair with MitraClip Device Considering the current interest to the new trans-catheter mitral valve repair, it has been our aim to investigate the remodeling of left ventricular (LV), left atrium (LA) and right ventricular (RV) in a cohort of 24 patients with severe organic (13 cases) or functional (11 cases) mitral regurgitation (MR), on a 6 months follow-up. Their mean age was 78, 54 ± 7, 64 years, and STS score 4, 69 ± 2, 39 and EuroSCORE II of 5, 10 ± 3, 28%, and a corresponding ASA score of 3, due to age, co-morbidity and impaired cardiac function (NHIA III/IV). In our study we used advanced techniques of 3D- echocardiography, for the advantage of images independent from the cutting sections, probe angles, and operators skills: this method accuracy is comparable to that of cardiac magnetic resonance imaging. In detail, all enrolled patients underwent transthoracic 3D, spackle tracking imaging, to assess valve anatomy, and suitability for MitraClip treatment according to the EVEREST anatomic eligibility criteria. They were on optimized medications and, when necessary, previously treated with percutaneous angioplasty and stent implantation. Our results, in both functional and organic cases of MV regurgitation, can be summarized in a statically significant improvement of the NHYA class, reduction in the degree of MV and tricuspid valve insufficiency, decrease in LV end-diastolic diameter and diastolic volume, and mainly in a corrected direction of LV outflow towards the high pressure aortic system: so we explain the unchanged left ventricular ejection fraction. The LA remodeling was present with a significant reduction in LA volume only in patients without atrial fibrillation, while in its function there was a reduced peak strain. Regard the indicative parameters of afterload on the right heart chambers, the derived systolic pulmonary arterial pressure decreased, and in case of tricuspid regurgitation, a significant decrease in the maximal velocity of the blood flow was observed. There was also a statistically significant reduction in the right atrial area, and in RV size, both correlated with a reduced back flow in the RA. About the RV volumetric remodeling there was no statistically significant improvement in the end-diastolic RV volume, most probably of its better compliance towards a low pressure inflow. An improvement in RV systolic function parameters was obtained in terms of increased ejection fraction, decreased free wall strain, and decreased velocity at the tricuspid annular. In Conclusion, the clinical improvement observed after Mitral Clip repair consist in decreased overload to the left chambers, facilitating their reverse remodeling, and in the LV function. In perspective, we are planning to perform pre-operative models of MV repair, where we can calculate the reduced volume of regurgitated blood and the increase in the LVEF physiological outflow, in order to better tailor the indications to this procedure.